DC Motor Speed Regulation Using Speech Recognition - Firda Andriyan Andriyan; Wahyu Sapto Aji (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
One of the uses of this sound technology is controlling the speed of a DC motor. Sound in the form of a spectrum signal can be converted to digital. Digital signals can be used as a microcontroller input to adjust the speed of a DC motor using the PWM (pulse width modulation) method. The design of the tool uses the V3 voice recognition module to convert the voice into digital. A microcontroller as a voice data processor by changing the input voltage to a DC motor. Voice command to set DC motor speed. Based on the results of tests carried out in good environmental conditions, 90% of voice commands can be recognized. Meanwhile, in bad environmental conditions by 50%. Manual measurement is done by entering the input voltage from 1 volt to 10 volts. The results of the comparison show that the speed is almost the same, namely 2727 rpm for manual calculation and 2915 rpm for the whole tool. This difference occurs because the test when manually inputting the tension is not very accurate. It can be concluded that the tool is working properly and as desired. If the environmental conditions are bad only 50% can be recognized from 30 voice commands, then there is a difference in voice intonation during the training process.